The Social Scientific Study of Islam in Indonesia: A 75 Year Retrospective - Hefner, Robert W. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2025)
This essay provides an historical overview of broad currents in the social scientific study of Islam in Indonesia from the Modjokuto project of the early 1950s to today. It makes three broad points. First, the essay shows that a perennial influence on the refiguration of Muslim politics and ethics in Indonesia has been, not scriptural principles alone, but the global ascendance of the modern nation state and Muslim intellectuals’ and politicians’ efforts to craft a Muslim public ethics consonant with the realities of a modern and religiously plural nation. Second, the essay shows that another feature of the social scientific study of Islam in Indonesia has been the ascendance of Indonesia-born Muslim intellectuals to positions of intellectual leadership in the field. Third, the overview makes clear that one of the most important recent achievements of this social scientific research has been to explain how Indonesia succeeded in developing the most effective and sustainable democracy in the Muslim-majority world.